Pelatihan Hidroponik untuk Meningkatkan Kreativitas Siswa dengan Memanfaatkan Barang Bekas - Wardani, Novia Kusuma; Nugroho, Syifa Alfina; Sulistyorini, Yunis; Sumitro, Nopem K.; Lestari, Purwaning Budi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2024)
The aim of this training was to provide students with knowledge in hydroponic plant cultivation. The background to this training was students' lack of knowledge in hydroponic plant cultivation and agricultural land was low. The participants involved in this training were grade 11 students of SMA Negeri 2 Negeri Katon, Pejambon Village, Negeri Katon District, South Lampung Regency, Lampung. The training implementation method included three stages, namely the socialization and counselling stage, the activity implementation stage and the reflection stage with training activity steps starting from socialization to students, making media charts from plastic bottles and cups, sowing plant seeds, continued with the implementation of hydroponic plant cultivation. The reflection stage was carried out after the implementation process by looking at the shortcomings and obstacles faced by students so that it can be carried out continuously and developed. This training is expected to be developed by students and teachers in order maintain the school environment, systems for utilizing school grounds and the surrounding environment, as well as increasing the creativity of students at grade XI in cultivating plants, especially vegetables, to meet daily nutritional needs.